2021
DOI: 10.21203/rs.3.rs-180732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Going Virtual: Youth Attitudes Toward and Experiences of Virtual Mental Health and Substance use Services During the COVID-19 Pandemic

Abstract: Background. During the COVID-19 pandemic, youth mental health and substance use services rapidly moved to virtual modalities to meet social distancing requirements. It is important to understand youth attitudes toward and experience of virtual services. Objective. This study examined the attitudes toward and experiences for virtual mental health and substance use services among youth drawn from clinical and non-clinical samples.Method. 409 youth completed a survey including questions about their attitudes towa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…A clear outcome of the pandemic for MHA services has been a shift to virtual care models, with many services rapidly adapting their approaches to be able to serve clients in light of existing protocols and limitations (e.g., [ 15 ]). While many participants enthusiastically shared the comfort and conveniences they experienced through virtual care, a finding consistent with other studies conducted during the pandemic [ 28 ], in the current study, there was a remarkably pervasive preference for in-person care as well as apprehensions toward virtual care. Attitudes toward virtual care were an important point of discussion around likelihood of participating in virtual care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A clear outcome of the pandemic for MHA services has been a shift to virtual care models, with many services rapidly adapting their approaches to be able to serve clients in light of existing protocols and limitations (e.g., [ 15 ]). While many participants enthusiastically shared the comfort and conveniences they experienced through virtual care, a finding consistent with other studies conducted during the pandemic [ 28 ], in the current study, there was a remarkably pervasive preference for in-person care as well as apprehensions toward virtual care. Attitudes toward virtual care were an important point of discussion around likelihood of participating in virtual care.…”
Section: Discussionsupporting
confidence: 88%
“…Attitudes toward virtual care were an important point of discussion around likelihood of participating in virtual care. Accordingly, prior work has highlighted positive youth attitudes toward virtual care as enabling participation, particularly for individual therapy rather than group support [ 28 ]. In the current study, this was not limited to the caregivers’ descriptions of the youths’ own attitudes toward virtual care—caregiver attitudes toward virtual care were also described as likely to influence the youth’s future participation in virtual care opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies to date have directly compared user and provider satisfaction, and there is scant research on Canadian experiences with this transition. 14,15…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 One study found no major effects on the overall frequency of substance use, but mixed effects for different substances, as well as changes in reasons and contexts of use. 20 …”
Section: Introductionmentioning
confidence: 99%